Transformation of alkanes under treatment of single impulse of hydrodynamic cavitation. II. Behaviour of medium-chain alkanes С21–С38 - V. N. Torhovsky; S. I. Vorobyev; E. V. Egorova; S. N. Antonyuk; S. N. Gorodsky; S. V. Ivanov (Тонкие химические технологии, 2014)
Transformation of medium-chain alkanes in the disintegrator DA-1 under treatment of single impulse of hydrodynamic cavitation has been studied. Cavitation appears when hydrocarbons pass through the micro-gap with controlled cross-section under high pressure. 5% solution of solid paraffin (alkanes C21–C38) in n-dodecane and two oil samples were used as objects of research. The first sample is partially stripped bituminous oil from Khosedauskoe field of Republic of Komi with paraffin content 0.5%wt. The second sample is mixture of above mentioned oil and paraffin with total concentration of the latter in this oil sample 6.5 %wt